Characterization of dielectric barrier discharge atmospheric air cold plasma treated gelatin films. (December 2015) - Pankaj, S.K.; Bueno-Ferrer, Carmen; Misra, N.N.; O'Neill, L.; Tiwari, B.K.; Bourke, Paula; Cullen, P.J.
Graphical abstract: Highlights: Evaluated the effects of in-package DBD plasma on gelatin film. AFM, XPS, contact angle, FTIR, XRD, OTR and WVTR were studied. Gelatin film is compatible with DBD plasma processes for food applications. Abstract: The aim of this work was to analyze the compatibility of bovine gelatin film with novel in-package dielectric barrier discharge atmospheric air plasma decontamination technology. Cold plasma treatment increased the roughness and topography of the treated film surface. It also increased the O/C ratio of the film surface by increasing the concentration of polar groups like COH and CO. This increase in the surface polarity was found to be the reason for increase in the hydrophilicity of the gelatin film and increased polar component of the surface free energy. Cold plasma treatment at higher voltage levels also increased the triple helical structure of the gelatin films. However, no significant changes were observed for any of the barrier properties of the film like water vapor and oxygen permeability.